2005
DOI: 10.1080/14992020500190235
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for development of severe tinnitus suffering-further characterisation

Abstract: The purpose of this study was to identify risk factors for Severe Tinnitus Suffering (STS) and to describe the results from psychiatric diagnostic interviews of STS positive and STS negative patients. Consecutive tinnitus patients (n = 127) completed the Nottingham Health Profile (NHP) and the Tinnitus Severity Questionnaire (TSQ) and answered general health questions at the first visit to the clinic and at eighteen months follow-up. Twenty-four months after the first tinnitus consultation, standardized diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
86
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 34 publications
12
86
2
7
Order By: Relevance
“…Regarding the incidence of tinnitus according to sex, there is no consensus in the literature. There are studies that showed a slight increase in the number of female subjects, justified by the greater availability and concern to seek medical assistance (20,21,22) ; however, other studies have suggested a prevalence in males due to excessive exposure to noise (23,24) , agreeing with the findings of this research.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the incidence of tinnitus according to sex, there is no consensus in the literature. There are studies that showed a slight increase in the number of female subjects, justified by the greater availability and concern to seek medical assistance (20,21,22) ; however, other studies have suggested a prevalence in males due to excessive exposure to noise (23,24) , agreeing with the findings of this research.…”
Section: Discussionsupporting
confidence: 80%
“…As for the syndromic distribution by gender, there was again a significant difference between the two, and the peripheral vestibular syndrome in the female gender was the most frequent, given the concordance with those reported in several studies [5,18,23]. Age groups aged 40 to 59 years and equal to or above 60 years had similar results, although some studies indicate that the majority of individuals complaining of dizziness are the elderly [3,23,24].…”
Section: Discussionsupporting
confidence: 69%
“…Age groups aged 40 to 59 years and equal to or above 60 years had similar results, although some studies indicate that the majority of individuals complaining of dizziness are the elderly [3,23,24]. It should therefore be taken into account that the mean and age of the female subjects (54.3 years) coincide with the menopause period [22].…”
Section: Discussionmentioning
confidence: 67%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Some have shown that the limitations due to tinnitus depend on primary psychological factors, such as difficulties in dealing with the problem, 8,12,[15][16][17] altered humor (depression and anxiety), low concentration, irritability, loss of control, 18 and a variety of psychiatric conditions and specific personality traits. 12,[15][16][17]19 Contrary to what was commonly thought, Jastreboff and Hazell 2 demonstrated that there are no psychoacoustic differences of tinnitus (intensity, frequency and minimum suppression level) among patients with tinnitus that suffer and those that do not. Other authors, however, have shown a small correlation between the intensity of tinnitus and its effect on patients.…”
Section: Introductionmentioning
confidence: 77%
“…Other authors, however, have shown a small correlation between the intensity of tinnitus and its effect on patients. [19][20][21] Thus, in medical practice, it is important to differentiate the intensity of tinnitus and how annoying it is for patients, since these parameters appear to correlate poorly. 11 The influence of hearing loss on the degree of suffering caused by tinnitus remains uncertain.…”
Section: Introductionmentioning
confidence: 99%